2007
DOI: 10.1007/s00421-007-0438-3
|View full text |Cite
|
Sign up to set email alerts
|

Is aerobic endurance a determinant of cardiac autonomic regulation?

Abstract: The aim of this study was to determine if subjects matched for VO2max but with differing aerobic endurance displayed similar heart rate variability (HRV) at rest and heart rate recovery (HRR) after maximal exercise. We hypothesized that the higher the aerobic endurance, the higher the HRV and the faster the HRR. Twenty-eight well trained middle- and long-distance runners (24 men and 4 women) performed a maximal continuous graded exercise test for the determination of maximal oxygen consumption (VO2max), ventil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
61
5
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 36 publications
7
61
5
6
Order By: Relevance
“…However, results are inconsistent and studies reported significant correlations as well as no correlations between VO 2max and the same HRV indicators (Bucheit and Gindre, 2006;Marocolo and Nadal, 2007;Bosquet and Gamelin, 2007;Kouidi et al, 2002;Sendelides et al, 2003). It is suggested that an explanation for the disparity could lie in the differences between the subjects investigated (Kouidi et al, 2002).…”
mentioning
confidence: 99%
“…However, results are inconsistent and studies reported significant correlations as well as no correlations between VO 2max and the same HRV indicators (Bucheit and Gindre, 2006;Marocolo and Nadal, 2007;Bosquet and Gamelin, 2007;Kouidi et al, 2002;Sendelides et al, 2003). It is suggested that an explanation for the disparity could lie in the differences between the subjects investigated (Kouidi et al, 2002).…”
mentioning
confidence: 99%
“…Bosquet et al [3] confirmed these findings in 28 middle-and long-distance runners (mean age 30-33 years, mean VO 2max 58-60 ml/kg per min). Buchheit and Gindre [4] studied 55 healthy subjects (mean age 30.8 ± 1.8 years) grouped according to their fitness level (assessed as VO 2max ) and training load (assessed by the Baecke sport score).…”
mentioning
confidence: 67%
“…Javorka et al [10] first reported a lack of association between the measured HRV and HRR in 17 untrained healthy men (mean age 20.3 ± 0.2 years, maximum power output 164 ± 5 W) in 2002. Bosquet et al [3] confirmed these findings in 28 middle-and long-distance runners (mean age 30-33 years, mean VO 2max 58-60 ml/kg per min). Buchheit and Gindre [4] studied 55 healthy subjects (mean age 30.8 ± 1.8 years) grouped according to their fitness level (assessed as VO 2max ) and training load (assessed by the Baecke sport score).…”
mentioning
confidence: 67%
“…Most of the studies on healthy populations showed the effects of physical training and HRV indices (Kawaguchi et al, 2007;Marocolo, Nadal & Barbosa, 2007;Melanson & Freedson, 2001;Rosenwinkel et al, 2001). However, other studies showed the opposite (Grant et al, 2013;Bosquet et al, 2007). Thus, the present study investigated another possibility of indices, based on HRV analysis, since it is already associated with physical fitness (Nasario-Junior et al, 2014;Nasario-Junior et al, 2015a).…”
Section: Introductionmentioning
confidence: 78%